(untitled) (Global Journal of Management and Business Research, 2025)
The role of Human Resource HR management in shaping business strategy and enhancing economic performance has evolved significantly This study explores how HR strategies can be integrated into business plans to drive organizational success Using the Resource-Based View and Human Capital Theory as theoretical frameworks the research examines the impact of HR practices such as talent management employee training and inclusion policies on financial performance metrics like profitability and productivity A mixed-methods approach combining quantitative surveys of 200 companies across various industries with qualitative case studies is employed to analyze the relationship between HR strategies and economic outcomes Findings indicate that strategic HR practices particularly talent management and training are positively associated with increased profitability and productivity The results suggest that effective HR strategies can be a significant driver of business success providing a competitive advantage through the optimal use of human capital However the study s limitations including industry-specific focus suggest areas for further research to explore long-term effects and applicability across different sectors